Individual memories and coping with the COVID-19 lockdown: Family members’ experiences - Shahin Salarvand; Masoumeh-Sadat Mousavi; Yadollah Pournia (Medwave, 2022)
Introduction Understanding the psychological and behavioral reactions to emerging infectious diseases is crucial in managing outbreaks. This study sought to explain family members’ experiences of individual memories and coping with the COVID-19 lockdown.